2016
DOI: 10.1027/2151-2604/a000253
|View full text |Cite
|
Sign up to set email alerts
|

Hindsight Bias and Law

Abstract: Abstract. Hindsight bias is the tendency to overestimate the foreseeability of an outcome once it is known. This bias has implications for decisions made within the legal system, ranging from judgments made during investigations to those in court proceedings. Legal decision makers should only consider what was known at the time an investigation was conducted or an offense was committed; however, they often review cases with full knowledge of a negative outcome, which can affect their judgments about what was k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 79 publications
0
21
0
Order By: Relevance
“…Several studies have demonstrated the occurrence of hindsight bias in the real world, such as in legal domains (for a review, see Giroux, Coburn, Harley, Connolly, & Bernstein, 2016), medical decision making (e.g., Arkes, 2013), economic fields (e.g., Biais & Weber, 2009), and ordinary decision making (Pieters, Baumgartner, & Bagozzi, 2006). Louie, Rajan, and Sibley (2007) reported a number of further real-world occurrences of hindsight bias and discussed their potential consequences (cf.…”
Section: Hindsight Biasmentioning
confidence: 99%
“…Several studies have demonstrated the occurrence of hindsight bias in the real world, such as in legal domains (for a review, see Giroux, Coburn, Harley, Connolly, & Bernstein, 2016), medical decision making (e.g., Arkes, 2013), economic fields (e.g., Biais & Weber, 2009), and ordinary decision making (Pieters, Baumgartner, & Bagozzi, 2006). Louie, Rajan, and Sibley (2007) reported a number of further real-world occurrences of hindsight bias and discussed their potential consequences (cf.…”
Section: Hindsight Biasmentioning
confidence: 99%
“…Both forms of conscious memory involve significant forgetting of the originally encoded information: in the case of semantic memory, students and teachers alike notice that learning for an exam is followed inevitably by massive forgetting of the initial information in the days and weeks after the exam; in the case of episodic memory, we tend to remember better the peak (most intense) and the end of a sequence of experience (the ‘peak-end’ rule; Kahneman, 2011), the personally relevant information rather than what is happening to strangers or distant others, as well as that which is vivid, striking, salient, as opposed to the mundane, the unsurprising, and the unemotional. The imperfections of episodic memory include the well-documented hindsight bias or the knew-it-all-along effect, which is the ‘tendency to overestimate the foreseeability of an outcome once it is known’ (Giroux et al, 2016: 190). The consensus view in cognitive science is that episodic memory is a (re)constructive process (Squire and Dede, 2015): we do not retrieve preexisting stored memories of events, but instead we recreate the memory of the event anew and modify it each time we attend to it: those components of a past situation we consciously recall get consolidated (strengthened synaptic links) whereas the unattended components become even more likely to be forgotten at the next attempt at recalling the situation (weakened synaptic links).…”
Section: Witnessed Situation Versus Remembered Situationmentioning
confidence: 99%
“…Evidence suggests that hindsight bias can manifest itself in the courtroom (for reviews of hindsight bias in legal decision making, see Giroux et al, 2016;Harley, 2007). In their seminal paper, Kamin and Rachlinski (1995) demonstrated among a sample of prospective jurors that precautionary measures to prevent damage from 1 There are several differences across jurisdictions regarding the degrees of freedom that directors typically get (for a comparison of the legislation across jurisdictions, see INSOL International, 2017), but a universality across legal systems is that for a director to be held liable, negligence and a causal link with the damages needs to be established.…”
Section: Hindsight Bias In Legal Judgmentsmentioning
confidence: 99%
“…Evidence suggests that hindsight bias can manifest itself in the courtroom (for reviews of hindsight bias in legal decision making, see Giroux et al., 2016; Harley, 2007). In their seminal paper, Kamin and Rachlinski (1995) demonstrated among a sample of prospective jurors that precautionary measures to prevent damage from possible flooding appear insufficient in hindsight, whereas in foresight (i.e., when the participants in the study were unaware flooding occurred) these measures were deemed largely appropriate (for similar findings, see Casper et al., 1988; Hastie et al., 1999; LaBine & LaBine, 1996; Lowe & Reckers, 1994).…”
Section: Introductionmentioning
confidence: 99%